2008
DOI: 10.1097/aud.0b013e31817a98af
|View full text |Cite
|
Sign up to set email alerts
|

The Electrically Evoked Auditory Change Complex: Preliminary Results from Nucleus Cochlear Implant Users

Abstract: Objectives-The purpose of this study was to determine if changes in the position of the stimulating electrode in the cochlea could be used to elicit the electrically evoked auditory change complex (EACC) from Nucleus cochlear implant users.Design-Nine postlingually deafened adults participated in this study. Each study participant had been using his or her Nucleus CI24 cochlear implant for at least 3 months prior to testing. The speech processor was bypassed and the output of the implanted receiver/stimulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
72
5
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 50 publications
12
72
5
3
Order By: Relevance
“…Brown et al (2008) described the eACC in response to changes in stimulating electrode position recorded from implanted adult listeners using direct-in stimulation. In this study, the speech processor microphone was bypassed and the electrical biphasic pulse train delivered directly to a single electrode using proprietary software.…”
Section: Introductionmentioning
confidence: 99%
“…Brown et al (2008) described the eACC in response to changes in stimulating electrode position recorded from implanted adult listeners using direct-in stimulation. In this study, the speech processor microphone was bypassed and the electrical biphasic pulse train delivered directly to a single electrode using proprietary software.…”
Section: Introductionmentioning
confidence: 99%
“…Though the ACC was first described more than thirty years ago by Jerger, it came into the focus of attention, during the last years, for evaluating the discrimination capabilities in cochlear implant subjects (Friesen & Tremblay, 2006;Brown et al, 2008;Martin, 2007;Kim et al, 2009). It was shown that the ACC may be recorded in cochlear implant subjects with minimal artefacts due to the electrical stimulation (Martin, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al demonstrated that smallest level differences may evoke an EACC (Kim et al, 2009). Brown et al (2008) have shown, that the EACC can be elicited by an electrical stimulus switching from one electrode to another. They postulated that the EACC can be used as an objective index for spatial resolution in cochlear implant subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Cortical auditory evoked potentials (CAEPs) to sounds mediated through a cochlear implant have been used to assess both the developing auditory system (Eggermont et al, 1997;Gilley et al, 2008;Gordon et al, 2005;Ponton et al, 1999), and the effects of stimulation on the mature auditory system (Brown et al, 2008;Friesen and Tremblay, 2006;Groenen et al, 2001;Pantev et al, 2002;Ponton et al, 1993;Purdy et al, 2001).…”
Section: Introductionmentioning
confidence: 99%